IFMBE Proceedings
DOI: 10.1007/978-3-540-73841-1_184
|View full text |Cite
|
Sign up to set email alerts
|

Verification of physical models used for root canal measurement by impedance comparison

Abstract: In the endodontic treatment of the root canal, one of the most important procedures is the root canal length determination. Apex-locators are commercial electronic devices used to determine canal length by measuring the electrical impedance. The verification of such instruments in-vivo is hard to perform because the only accurate way of measurement is by extracting the tooth and then measuring the canal length. For this reason, testing of apex-locators and their comparison as well as new measuring method evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…However, some of these materials might give greater accuracy than can be accomplished in vivo (26). Moreover, Marjanovic et al (27) observed that there are significant differences in electrical properties between in vitro and in vivo models. In light of these findings, extrapolation from in vitro studies to the clinical setting might not be appropriate.…”
mentioning
confidence: 97%
“…However, some of these materials might give greater accuracy than can be accomplished in vivo (26). Moreover, Marjanovic et al (27) observed that there are significant differences in electrical properties between in vitro and in vivo models. In light of these findings, extrapolation from in vitro studies to the clinical setting might not be appropriate.…”
mentioning
confidence: 97%
“…After that, the tooth has been immersed in freshly mixed alginate prior to the hardening of the material. The alginate material is widely used as a physical model for in vitro measurements [2,4,12,15] since it has adequate physical and electrical properties. We have used Fast Set alginate dental impression material by GC Europe n.v. (Leuven, Belgium) prepared according to manufacturer's instructions using tap water.…”
Section: Tooth Fixation and Impedance Measu-rementmentioning
confidence: 99%
“…Prior to this study we have used equivalent circuits with two or three linear elements (resistors and capacitors) to model the tooth [8,10,[12][13][14][15]. They could represent impedance behavior in a narrow frequency range, but their elements had to be frequency dependent in order to describe impedance in wider frequency range.…”
Section: Evaluated Electrical Equivalent Circuitsmentioning
confidence: 99%
See 1 more Smart Citation